Dimension estimation for autonomous nonlinear systems - Padoan,A; Astolfi,A (IEEE, 2015)
The problem of estimating the dimension of the state-space of an autonomous nonlinear system is considered. Assuming that sampled measurements of the output and finitely many of its time derivatives are available, an exhaustive search algorithm able to retrieve the dimension of the minimal state-space realization is proposed. The performance of the algorithm are evaluated on specific nonlinear systems.